Serum biomarkers for early detection of gynecologic cancers - Ueda, Yutaka; Enomoto, Takayuki; Kimura, Toshihiro; Miyatake, Takashi; Yoshino, Kiyoshi; Fujita, Masami; Kimura, Tadashi (REPRODUCTIVE ENDOCRINOLOGY, 2013)
Ovarian, endometrial, and cervical cancers are three of the most common malignancies of the female reproductive organs. CA 125, historically the most reliable serum marker for ovarian cancer, is elevated in 50% of early-stage ovarian tumors. For endometrial cancers, there are no established serum markers. SCC, which is the best studied serum marker for squamous cell carcinomas, has been unreliable; SCC is elevated in cervical squamous cell carcinomas ranging from 28–85% of the time. Recent proteomics-based analyses show great promise for the discovery of new and more useful biomarkers. In this review, we discuss the currently utilized serum tumor markers for gynecologic cancers and the novel biomarkers that are now under investigation.